THE IMPACT OF REGULAR PHYSICAL ACTIVITY ON STUDENTS’ ACADEMIC PERFORMANCE - Z.B.Khodjayeva (International Journal of Literature and Language Studies, 2026)
Physical activity is widely recognized as an essential component of a healthy lifestyle. In recent years, researchers and educators have become increasingly interested in the relationship between physical activity and academic achievement among students. The purpose of this study is to examine the impact of regular physical activity on students’ academic performance. The study investigates whether participation in sports and exercise contributes to improved concentration, memory, motivation, and overall educational outcomes. The findings suggest that students who engage in regular physical activity demonstrate better academic performance compared to their less active peers. The results highlight the importance of integrating physical education and sports programs into educational institutions.